Recognition of Emotions in Video Clips: The Self-Assessment Manikin Validation - Dini Handayani; Abdul Wahab; Hamwira Yaacob (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Many research domains use video contents as stimuli for study on human emotions. A video content within a particular genre or a specific theme evokes dynamic emotions that are highly useful in many research fields. The present study proposed a set of video-clip stimuli that embody four emotions under specific genres of movies, namely happiness, calmness, sadness and fear. Two experiments (a preliminary and a validation) were conducted in order to validate the video clips. Self-Assessment Manikin was utilized to rate the videos. All the video clips were rated with respect to valence and arousal judgment. In the preliminary experiment, the video clips were rated in terms of how clearly the expected emotions were evoked. The validation experiment was conducted to confirm the results from preliminary experiment, and only video clips with high recognition rates were included into data set.